2021
DOI: 10.1186/s13052-021-01015-6
|View full text |Cite
|
Sign up to set email alerts
|

“Impact of COVID-19 pandemic lockdown on early onset of puberty: experience of an Italian tertiary center”

Abstract: At the end of 2019, an emerging atypical pneumonia called COVID-19 (coronavirus disease 2019), caused by the novel coronavirus defined as SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2), was first reported. COVID-19 rapidly expanded leading to an epidemic in China, followed by a global pandemic during the year 2020. In few weeks Italy was assaulted by a severe health emergency, constraining the Italian government to put in place extraordinary restrictive measures, such as school closures and a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
58
2
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 4 publications
13
58
2
11
Order By: Relevance
“…Since mid 2020 several centers of pediatric endocrinology in Italy, including ours, have observed a significant increase in the number of female patients presenting with precocious puberty, precocious menarche, and rapidly progressing puberty. Until now these observations have been reported by the Meyer Hospital in Florence just after the lockdown (1), and very recently by the main pediatric hospital in Rome in a letter to the Editor (2). The first report observed an increase in the number of diagnoses and an acceleration in the progression of puberty, and hypothesized that this phenomenon was associated with the increased use of electronic devices and increased body mass index (BMI) subsequent to reduced physical activity and possibly increased eating.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Since mid 2020 several centers of pediatric endocrinology in Italy, including ours, have observed a significant increase in the number of female patients presenting with precocious puberty, precocious menarche, and rapidly progressing puberty. Until now these observations have been reported by the Meyer Hospital in Florence just after the lockdown (1), and very recently by the main pediatric hospital in Rome in a letter to the Editor (2). The first report observed an increase in the number of diagnoses and an acceleration in the progression of puberty, and hypothesized that this phenomenon was associated with the increased use of electronic devices and increased body mass index (BMI) subsequent to reduced physical activity and possibly increased eating.…”
Section: Introductionmentioning
confidence: 95%
“…Nutrition is a known driver of sexual maturation ( 18 ). In malnourished adopted children a significant weight increase is well known to trigger precocious puberty ( 19 21 ), however, although during the pandemic BMI has generally increased because of reduced physical activity often this increase is not so significant ( 1 , 2 ), and above all, none of these girls were malnourished before the pandemic. Therefore, it is unknown whether a modest increase in BMI alone could explain an increased frequency of cases of precocious puberty observed in clinics.…”
Section: Nutrition Adiposity and Physical Activitymentioning
confidence: 99%
“…similarly, in the second study, a rise in referrals for suspected precocious puberty was recorded in 2020 (+ 108% consultations compared to 2019) [17]. These results seem to suggest a possible role of environmental factors on the early onset of puberty during COVID-19 pandemics.…”
Section: Discussionmentioning
confidence: 61%
“…Finally, a significant increase of cases of central precocious puberty and a faster pubertal progression in girls has been reported since the beginning of COVID-19 pandemic [ 36 , 37 ]. This might be related to multiple environmental triggers, including the increase in fat mass, the prolonged exposure to electronic devices, as well as the psychological stress itself [ 36 ], whose role in acceleration of puberty timing proposed in past studies [ 38 ] remains to be demonstrated.…”
Section: Immediate Consequencesmentioning
confidence: 99%